THAILAND STUDENTS’ DIFFICULTIES AND MOTIVATION IN STUDYING BIPA AT UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - Srikandi, Cut Novita (Jurnal As-Salam, 2022)
This study was conducted to identify the difficulties, challenges, and motivations of foreign students studying Bahasa at the Universitas Muhammadiyah Sumatera Utara (UMSU). This research was conducted by taking data from 12 foreign students from Thailand who took part in the Bahasa Indonesia Bagi Penutur Asing (BIPA) program at UMSU as research respondents. Observations, questionnaires, and interviews were used as research materials to obtain data and analyzed using the descriptive qualitative method by looking at the percentage only. The results showed that there were several difficulties faced by BIPA students, including; difficulty pronouncing some phonemes in Bahasa; lack of time both in learning and practicing Bahasa; lack of confidence to speak Bahasa; challenging teaching materials, students’ cultural background; the different languages of the learners; and the lack of additional resources that can be accessed online. It was also found that the respondents had a positive attitude and high motivation when learning Bahasa. Further findings indicate that BIPA teachers’ role also motivates students to learn Bahasa. Overall, foreign students have a positive attitude and high motivation to learn Bahasa if they get encouragement and guidance from the teacher and the surrounding environment.